Haematological Profile and Serum Biochemistry of Juvenile Clarias gariepinus as Biomarkers of Textile Wastewater Toxicity - Durojaiye, Abiola; Ojetayo, Teslim Asafe; Adedeji, Helen Oluwaseun (Jurnal Perikanan Universitas Gadjah Mada, 2024)
Pollution is a global problem with hazardous consequences especially on the biotic components of the aquatic ecosystem. Blood is a useful tool in diagnosing the health condition of fish. Hence, the aim of this project was to evaluate the effect of textile wastewater on fish blood. Fish were exposed to varying concentrations of textile wastewater for 96 hours. There were four treatments including the control and others containing 0.0005 ppm, 0.002 ppm and 0.035 ppm of textile wastewater per every 35 litres of freshwater. Each treatment had one replicate with 5 fish stocked in each replicate. The textile effluent significantly reduced (p<0.05) red blood cells (RBC), packed cell volume (PCV), haemoglobin concentration (HGB), and white blood cell (WBC) in the other treatments compared to the control. However, the mean corpuscular volume (MCV), mean corpuscular haemoglobin (MCH), and mean corpuscular haemoglobin concentration (MCHC) were not statistically different (p>0.05) from the control. There was a significant reduction in the value of serum metabolites (total protein, globulin, glucose) of juvenile C. gariepinus after exposure to textile effluent (p<0.05). Urea, albumin, and cholesterol increased significantly (p<0.05). However, creatinine did not follow any specific trend across the treatments. The activities of Aspartate transaminase (AST) and Alkaline transaminase (ALT) were significantly higher in the exposed fish compared to the control (p<0.05). Alkaline phosphatase (ALP) recorded a significantly higher value in the control compared to the other treatments (p<0.05). There were no significant differences in the concentrations of both Superoxide dismutase (SOD) and Glutathione S-transferase (GST) of fish exposed to textile effluent (p>0.05). The result revealed that the textile wastewater adversely affected the blood components of the exposed fish. It can be concluded that the presence of textile wastewater in aquatic environments could induce stress and consequently deteriorate the health of aquatic organisms.